Cracking the relation between mass and 1P star fraction of globular clusters$bI. present-day cluster masses as a first tool - Parmentier, Geneviève (The astrophysical journal, 2024)
The phenomenon of multiple stellar populations is exacerbated in massive globular clusters, with the fraction of first-population (1P) stars a decreasing function of the cluster present-day mass. We decipher this relation in far greater detail than has been done so far. We assume (i) a fixed stellar mass threshold for the formation of second-population (2P) stars, (ii) a power-law scaling between the mass m ecl of newly formed clusters and their 1P star fraction F 1P, and (iii) a constant F 1P over time. The F 1P(m ecl) relation is then evolved up to an age of 12 Gyr for tidal field strengths representative of the entire Galactic halo. The 12 Gyr old model tracks cover the present-day distribution of Galactic globular clusters in the (mass, F 1P) space extremely well. The distribution is curtailed on its top right side by the scarcity of clusters at large Galactocentric distances and on its bottom left side by the initial scarcity of very high-mass clusters and dynamical friction. Given their distinct dissolution rates, “inner” and “outer” model clusters are offset from each other, as observed. The locus of Magellanic Clouds clusters in the (mass, F 1P) space is as expected for intermediate-age clusters evolving in a gentle tidal field. Given the assumed constancy of F 1P, we conclude that 2P stars do not necessarily form centrally concentrated. We infer a minimum mass of 4 · 105 M ⊙ for multiple-population clusters at secular evolution onset. This high-mass threshold severely limits the number of 2P stars lost from evolving clusters, thereby fitting the low 2P star fraction of the Galactic halo field.